Serum Progranulin Levels in Type 2 Diabetic Patients with Metabolic Syndrome - Shafaei Azam; Marjani Abdoljalal; Khoshnia Masoud (Sciendo, 2016)
Introduction. The role of progranulin in individuals with metabolic syndrome is not exactly clear.We aimed to assess the serum level of progranulin in type 2 diabetic patients with and without metabolic syndrome and compare them with healthy controls.